miRNA in blood-brain barrier repair: role of extracellular vesicles in stroke recovery - Sprincl, Vojtech; Romanyuk, Nataliya (Frontiers in Cellular Neuroscience, 2025)
Ischemic stroke is a leading cause of mortality and long-term disability globally. One of its aspects is the breakdown of the blood-brain barrier (BBB). The disruption of BBB’s integrity during stroke exacerbates neurological damage and hampers therapeutic intervention. Recent advances in regenerative medicine suggest that mesenchymal stem cells (MSCs) derived extracellular vesicles (EVs) show promise for restoring BBB integrity. This review explores the potential of MSC-derived EVs in mediating neuroprotective and reparative effects on the BBB after ischemic stroke. We highlight the molecular cargo of MSC-derived EVs, including miRNAs, and their role in enhancing angiogenesis, promoting the BBB and neural repair, and mitigating apoptosis. Furthermore, we discuss the challenges associated with the clinical translation of MSC-derived EV therapies and the possibilities of further enhancing EVs’ innate protective qualities. Our findings underscore the need for further research to optimize the therapeutic potential of EVs and establish their efficacy and safety in clinical settings.